2017
DOI: 10.1371/journal.pone.0183557
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic benefits of intravenous cardiosphere-derived cell therapy in rats with pulmonary hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a progressive condition characterized by occlusive pulmonary arteriopathy, in which survival remains poor despite pharmacologic advances. The aim of this study was to evaluate the ability of cardiosphere-derived cells (CDCs), cardiac progenitor cells with potent anti-inflammatory and immunomodulatory properties, to attenuate hemodynamic and morphometric remodeling of the right ventricle (RV) and pulmonary arterioles in rats with established monocrotaline (MCT)-induced P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…The time course studies revealed that a signi cant increase in RV systolic pressure predated the development of RV hypertrophy in PAH animals, like that described in previous studies [30,34]. This suggests that pressure overload was an important early stimulus to RV hypertrophy in an adaptive fashion.…”
Section: Adaptive Rv Hypertrophysupporting
confidence: 79%
“…The time course studies revealed that a signi cant increase in RV systolic pressure predated the development of RV hypertrophy in PAH animals, like that described in previous studies [30,34]. This suggests that pressure overload was an important early stimulus to RV hypertrophy in an adaptive fashion.…”
Section: Adaptive Rv Hypertrophysupporting
confidence: 79%
“…CDCs have been shown to promote tissue repair in several preclinical studies, including a DMD mouse model (11,13,(17)(18)(19)(20). Much of the previous work has focused on studying the therapeutic benefits associated with direct myocardial delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to small sample sizes, statistical tests for comparison were not performed. Categorical data presented as total count and percentage (%), and continuous data are presented as mean ± standard deviation (SD) These anti-inflammatory effects have been demonstrated in animal models of myocardial ischemia, myocarditis, muscular dystrophy, aging, heart failure with preserved ejection fraction, pulmonary arterial hypertension and dilated cardiomyopathy [3,20,21,33,34,42]. Finally, based on preclinical work, a majority of IV CDCs are retained in the lungs [6].…”
Section: Discussionmentioning
confidence: 99%